Kajian proporsi santan kelapa, umbi gembili dan penambahan volume buah naga merah terhadap karakteristik fisikokimia serta organoleptik es krim nabati - Andre Ferdiansyah; Sri Winarti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Ice cream is a food that is generally made from cow's milk as a source of fat, but cow's milk can be bound by coconut milk as a source of fat because it has a chemical composition that almost resembles milk. Gembili can also be used as an additive in making ice cream because it contains glucomannan-type glycoprotein and water-soluble polysaccharide , which is a type of bioactive compound that acts as a water-soluble food fiber and is hydrocolloid. In addition to taste, taste and texture, color also affects the quality of ice cream. Dragon fruit can be chosen as a fortification that can make the appearance of ice cream more attractive. This study aims to determine the effect of the proportion of coconut milk and gembili pulp with the addition of red dragon fruit on the physicochemical and organoleptic qualities of making vegetable ice cream. This study used a two-factor Completely Randomized Design (CRD). The first factor was the proportion of coconut milk and gembili porridge, respectively 25:75, 50:50, 75:25. The second factor is the addition of dragon fruit, namely 15%, 20% and 25%. Observational data were analyzed using ANOVA, if there was an interaction or a significant effect on the two treatments then a 5% DMRT best treatment results is proportion of coconut milk: gembili slurry (75:25) and 25% dragon fruit with an average melting time of 14.29 ± 0.113 minutes/20gr, viscosity 173.0 ± 1.414, total solids 15.67 ± 0.289, overrun 35.70 ± 0.208, fat content 6.23 ± 0.042, protein content 8.44 ± 0.113, antioxidant content 65.80%, dietary fiber 4.34% 7.90, a = 79.55, B = 0.45), organoleptic hedonic aroma 3.06, taste 4.08, color 3.72 and texture 2.96.